The Influence of Pandawara's Tiktok Media Exposure on People's Environmental Awareness - Azmar, Rahma Nurshani; Bahfiarti, Tuti; Mau, Muliadi (IHSA Institute, 2024)
The purpose of this study is to analyze the level of environmental awareness behavior among followers of the Pandawara TikTok account. The study lasted approximately three months, from October to November 2023. Quantitative methods were employed using survey techniques. Data collection involved distributing questionnaires and conducting literature studies, including scientific journals, books, and other relevant sources. The population consisted of followers of the Pandawara TikTok account, totaling 7.6 million accounts. The research sample was determined using Probability Sampling with a simple random sampling method, resulting in a sample size of 399 accounts based on the Slovin formula with a 5% error rate. Data analysis included validity tests, reliability tests, and simple linear regression tests, conducted using IBM SPSS application version 24. The results indicated that the level of public environmental awareness behavior on the Pandawara TikTok account fell within the medium category, accounting for 70.1% of respondents